The theoretical model of spatial production for innovation - Daniel Olah; B. Levente Alpek (Journal of Innovation and Entrepreneurship, 2021)
The overall aim of the study is to create the theoretical model of spatial production for innovation, which provides a measurement basis for later research as well as providing a measurement framework for the territorial indexation of innovation. In addition, it raises the question of what factors can hinder and which can help the formation and development of the spatial production of innovation. In the context of the above, based on a chronological, multidimensional review and analysis of literature research, it summarizes and presents the possibilities of interpreting the concept of innovation, paying attention to its territorial aspects. The model presented in our study builds on the literature on the external-internal divisions of innovation barriers, but also differs in that the model simultaneously displays the socio-economic space (innovation ecosystem), the regional scales as well as time. Presenting the typological barriers to innovation and summarizing the related factors, as well as developing a model to measure the issue, can help by specifically promoting the development of regions with less innovation capacity and potential in this field, at the same time providing a basis for assessing the territorial aspects of the phenomenon, which may also support the creation of development programmes to support the resolution of territorial disparities.
Keywords: O31; 650; Innovation; Innovation geography; Geography of innovation; Barriers toinnovation